Social Pressure: Motif dan Alasan Anak Melakukan Aborsi - Larasati, Yuniar Galuh; Abdullah, Irwan (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
Social pressure is a phenomenon that often leads minors to choose abortion. Studies that have discussed this phenomenon only focus on the context of law enforcement, so they have not comprehensively explained the social pressure that drives children to have abortions. This study focuses on the question